Snapshots of scorpion venomics. (January 2015) - Abdel-Rahman, Mohamed A.; Harrison, Patrick L.; Strong, Peter N.
Abstract: Scorpions are particularly well adapted to survival in extreme habitats (especially arid and semi-arid environments) and their ability to produce and deliver venoms is an important factor in this success. Scorpion venoms are very complex mixtures of different proteins and peptides. Previous venomics studies revealed that each one of scorpion species may contain more than 100 different peptides. Scorpion venom peptides can be classified into two main types: disulfide-bridged peptides (DBPs) and non-disulfide-bridged peptides (NDBPs). The vast majority of DBPs are neurotoxic peptides that specifically interact with various types of ion-channels. The NDBPs have been shown to variously possess bradykinin-potentiating, antimicrobial, hemolytic, cellular signaling and immune-modulating activities. Recently, venom proteomics have been extensively applied in assessing the diversity of scorpion venom from various species. More insights about scorpion venom compositions were also gained through transcriptomic approach. It has provided an opportunity to obtain an overview of the content of scorpion venoms and to compare the relative abundance of toxin transcripts. More importantly, transcriptomics can reflect the biological processes occurring in venom gland cells. This review will highlight recent proteomic and transcriptomic studies to explore the venome of scorpions from different habitats, focusing on desert scorpions from North Africa. Highlights: We discussed recent proteomic and transcriptomic approaches used to analyze scorpion venoms. To date, over 800 scorpion venom peptides have been identified. About 40, 000 ESTs have been characterized from 17 different scorpion species. More venomics studies needed for scorpions inhabiting the Sahara desert.